2012
DOI: 10.1097/ppo.0b013e31826c57f1
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Cutaneous Peripheral T-Cell Lymphomas

Abstract: The cutaneous T-cell lymphomas are a heterogeneous collection of many biologically and clinically distinct cancers. The World Health Organization 2008 reclassification of cutaneous lymphomas delineated provisional entities that were previously classified simply as primary cutaneous peripheral T-cell lymphoma not otherwise specified. Because of the relative rarity of cases, standard treatment recommendations and algorithms are lacking. However, identification of these subtypes is important as they can have vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In conclusion, it is crucial to recognize this novel entity among the spectrum of CD8+ cytotoxic lymphoid proliferations and to clearly differentiate it from otherwise unfavorable CD8+ cutaneous peripheral T‐cell lymphomas to avoid an unnecessary aggressive treatment for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, it is crucial to recognize this novel entity among the spectrum of CD8+ cytotoxic lymphoid proliferations and to clearly differentiate it from otherwise unfavorable CD8+ cutaneous peripheral T‐cell lymphomas to avoid an unnecessary aggressive treatment for the patients.…”
Section: Discussionmentioning
confidence: 99%
“…PTCL-NOS is a subtype of PTCL that is aggressive and predominantly nodal. Patients with PTL-NOS may present with a nodule that is solitary like a red tumor ineffective for PTL-NOS therapy and can lead to worsening conditions [17]. Even with systemic chemotherapy and stem cell transplantation, the prognosis is still inferior in PTL-NOS cases [18].…”
Section: Discussionmentioning
confidence: 99%
“…Since PTL-NOS presents in such an aggressive nature, most other treatments for CTCL such as interferon-alpha, retinoids, PUVA light therapy, and localized radiotherapy are bypassed [ 7 ]. Studies have shown that cytokine treatments such as interferon-alpha, which are useful in Mycosis Fungoides and Sezary Syndrome, not only are ineffective in PTL-NOS, but may also exacerbate the condition [ 8 ]. Even with systemic chemotherapy and stem cell transplantation, prognosis is unfortunately still very poor for patients with PTL-NOS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%